Students' Anxiety in Language Learning - Nurhaeni Nurhaeni (EDUVELOP, 2019)
It has been widely admitted that most people have their own obstacles when it comes into learning a new language. In fact, it happens to students a lot. Some studies have been conducted in order to investigate further about the students’ anxiety level in learning language. There are some anxiety factors that have been explored, discussed, and analyzed in order to find the solution on overcoming the anxiety problem. This research is intended to explore the influence of gender (male and female) in the anxiety issue of learning language. The participants of this research consisted of 45 male and 45 female students in one Junior High School in West Java. This research applied FLCAS questionnaire to explore students’ level of anxiety. Based on the data analysis through the questionnaire, it is found that there is no difference between male and female students in terms of their anxiety in language learning. It is proven by the chi-square test that is applied to analyze the data collected.